PREVENTING PERIPHERAL ARTERIAL DISEASE: THE CRUCIAL ROLE OF CARDIOLOGISTS. - Kumar, Abilesh (Student’s Journal of Health Research Africa, 2023)
Peripheral artery disease (PAD) is a clinical appearance of systemic atherosclerotic disease. Individuals diagnosed with PAD exhibit an unfavorable prognosis characterized by an elevated susceptibility to cardiovascular (CV) occurrences, such as stroke, myocardial infarction, limb ischemia, and cardiovascular mortality. Consequently, the timely identification and management of PAD assume paramount significance. PAD and CAD (coronary artery disease) exhibit a shared pathogenesis and risk elements, thereby conferring upon cardiologists a distinct advantage in the screening, diagnosis, and management of PAD. Furthermore, PAD and CAD exhibit overlapping treatment objectives, which encompass a proactive alteration of risk elements to mitigate the likelihood of cardiovascular events. PAD continues to be a condition that is frequently overlooked in terms of diagnosis and treatment, resulting in potential legal ramifications within the medical field. The objective of this review is to raise alertness among clinicians concerning the importance of PAD, as the responsibilities of cardiologists continue to broaden. Recognizing the systemic nature of PAD and its association with adverse cardiovascular outcomes underscores the importance of early diagnosis and proactive management. Future research, interdisciplinary collaboration, and policy development should all aim to improve the identification and care of individuals with PAD, ultimately reducing the burden of cardiovascular events and enhancing patient care.